Development of a robust and efficient virus-induced gene silencing system for reverse genetics in recalcitrant Camellia drupifera capsules - Hongjian Shen; Huajie Chen; Weimeng Li; Shan He; Boyong Liao; Wanyu Xiong; Yang Shen; Yongjuan Li; Yanru Gao; Yong Quan Li; Bipei Zhang (Plant Methods)
Abstract Background Virus-induced gene silencing (VIGS) is a rapid and powerful method for gene functional analysis in plants that pose challenges in stable transformation. Numerous VIGS systems based on Agrobacterium infiltration has been widely developed for tender tissues of various plant species, yet none is available for recalcitrant perennial woody plants with firmly lignified capsules, such as tea oil camellia. Therefore, there is an urgent need for an efficient, robust, and cost-effective VIGS system for recalcitrant tissues. Results Herein, we initiated the Tobacco rattle virus (TRV)-elicited VIGS in Camellia drupifera capsules with an orthogonal analysis including three factors: silencing target, virus inoculation approach, and capsule developmental stage. To facilitate observation and statistical analysis, two genes predominantly involved in pericarp pigmentation were selected for silencing efficiency: CdCRY1 (coding for a key photoreceptor affecting light-responsive perceivable anthocyanin accumulation in exocarps) and CdLAC15 (coding for an oxidase catalyzing the oxidative polymerization of proanthocyanidins in mesocarps, resulting in unperceivable red-hued mesocarps). The infiltration efficiency achieved for each gene was ~ 93.94% by pericarp cutting immersion. The optimal VIGS effect for each gene was observed at early (~ 69.80% for CdCRY1) and mid stages (~ 90.91% for CdLAC15) of capsule development. Conclusions Using our optimized VIGS system, CdCRY1 and CdLAC15 expression was successfully knocked down in Camellia drupifera pericarps, leading to fading phenotypes in exocarps and mesocarps, respectively. The established VIGS system may facilitate functional genomic studies in tea oil camellia and other recalcitrant fruits of woody plants.